2019
DOI: 10.1021/acs.jpcc.9b05785
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Charge Carrier and Coherent Acoustic Phonon Dynamics of Black Phosphorus Studied by Transient Absorption Microscopy

Abstract: Due to its corrugated hexagonal lattice structure, Black phosphorus (BP) has unique anisotropic physical properties, which provides an additional freedom for designing devices. Many body interactions, including interactions with phonon, is crucial for heat dissipation and charge carrier mobility in device. However, the rich properties of the coherent acoustic phonon, including anisotropy, propagation and generation were not fully interrogated. In this paper, the polarization-resolved transient absorption micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…It can be seen that the PA peak gradually grows, eventually reaching a maximum in the order of ≈10 2 ps. According to a previous report, [12] we identified that this phenomenon is caused by the absorption of excited states, which highlights a feature of positive absorption change. At the same time, we found an overlaying PA peak near 2.06 eV, which indicates a resonance position conducive to ESA absorption in the I-scan.…”
Section: Transient Absorption Spectra and Dynamicssupporting
confidence: 57%
See 1 more Smart Citation
“…It can be seen that the PA peak gradually grows, eventually reaching a maximum in the order of ≈10 2 ps. According to a previous report, [12] we identified that this phenomenon is caused by the absorption of excited states, which highlights a feature of positive absorption change. At the same time, we found an overlaying PA peak near 2.06 eV, which indicates a resonance position conducive to ESA absorption in the I-scan.…”
Section: Transient Absorption Spectra and Dynamicssupporting
confidence: 57%
“…Similar to other 2D materials such as graphene, [1][2][3] transition metal chalcogenides (TMDCs), [4][5][6][7] and topological insulators, [8,9] black phosphorus (BP) [10][11][12][13][14] have aroused extensive research enthusiasm in various fields. Possessing excellent properties, BP exhibits excellent potential for applications in electronics, [15] optoelectronics, [16][17][18][19] thermoelectrics, [20] photo biology, [21] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency depends linearly on the inverse of the probe wavelength and lies in the tens of GHz range, as shown in Figure 7 b, in strong contrast to the previously reviewed COPs. Such phenomenon has been observed in thick exfoliated Re 6 Se 8 Cl 2 (see Figure 6 ) [ 142 ], BP [ 125 ], MoS 2 (see Figure 7 ) [ 143 ], Bi 2 Se 3 [ 39 , 235 ], and Bi 2 Te 3 [ 138 ], which all are semiconducting vdW materials with interestingly different 2D lattice structures. In these examples, samples are pumped above their respective bandgap yielding pump penetration depths evaluated in the 100-nanometers range or below, and significantly smaller than the slab thicknesses.…”
Section: Coherent Phonons In Vdw Materialsmentioning
confidence: 78%
“…In this context, due to incorrect assignments of echo instead of single trip delays in the oscillation (see below) and of the corresponding resonant acoustic mode (see Section 4.4 ), a value twice higher than expected for v and thus one twice lower for n pr , are reported in MoS 2 in Reference [ 143 ]. Interestingly, the optical anisotropy in BP leads to slightly different optical indices for orthogonal probe polarizations, which induces different Brillouin frequencies even though the same propagating CAP with a single given velocity is probed [ 125 ].…”
Section: Coherent Phonons In Vdw Materialsmentioning
confidence: 99%
See 1 more Smart Citation